Digital Humanities in Islamic Manuscript Studies: Opportunities and Challenges of the DREAMSEA Repository for Master’s Research - Karim, Moh Mujib; Maulidi, Affan; Kamal, Yusuf (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The development of Digital Humanities is driving transformation in the study of Islamic manuscripts through the digitization and use of online repositories such as the DREAMSEA Platform (Digital Repository of Endangered and Affected Manuscripts in Southeast Asia). Although access to manuscripts is increasing, their use in research remains predominantly descriptive and has not been fully integrated into the methodological framework of philology. This research aims to analyze the opportunities and limitations of digital manuscripts and determine their position in philological studies. The method used is qualitative research based on literature studies with an analysis of scientific literature and digital manuscripts. The results of the study show that digital manuscripts offer significant opportunities, including increased access to primary sources, greater efficiency in data exploration, and the development of technology-based interdisciplinary approaches such as corpus analysis and artificial intelligence. However, there are fundamental limitations, including the loss of aspects of manuscript materiality, issues of the text's authenticity and authority, visual reproduction quality that is not always optimal, and limited digital manuscript variants available. These findings confirm that digital manuscripts cannot replace physical manuscripts in in-depth philological analysis, but rather serve as complementary sources, especially at the heuristic and exploratory stages. Therefore, an integrative approach is needed that balances the efficiency of digital technology with the methodological rigor of philology to optimize humanities research in the digital era. Keywords: Digital Humanities, Islamic Manuscripts, Philology, Digitization of Manuscripts, Digital Repositories, DREAMSEA